Identity of the East End City Identity of the East End City of Java Island: Endhog-Endhogan Tradition in Banyuwangi in Commeration of the Birthdayof Prophet Muhammad SAW - Pratama, Moch. Sholeh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
This study presents a study of city identity in the aspect of non-physical objects (religious social activities) in Banyuwangi, namely the endhog-endhogan tradition on the commemoration of the birthday of the Prophet Muhammad SAW. A tradition that is one of the (positive) identities of the City of Banyuwangi pioneered by KH Abdullah Faqih, the founder of the Cemoro Islamic Boarding School, Songgon. The endhog-endhogan tradition is a form of visualization of the birth of the Prophet Muhammad SAW, before the birth of the Prophet Muhammad SAW the Arabian peninsula was hit by famine, but after the Prophet Muhammad SAW was born flowering and fruiting plants. This research is written using historical research methods, the data obtained from the Pegon Community, a historical community in Banyuwangi, interviews with the family of KH. Abdullah Faqih Cemoro, and supporting literature in the form of scientific writings. In this paper, the profile and intellectual genealogy of KH. Abdullah Faqih Cemoro, the historicity and philosophy of the endhog-endhogan tradition, and how the endhog-endhogan tradition has become an identity for the people and the city of Banyuwangi. All of them are presented considering that the identity or image of the city is strongly related to the historical aspects that are